Effectiveness and potential drug interactions in antiviral therapy for the treatment of chronic hepatitis C: real-life data from a specialized center in southern Brazil (Brazilian Journal of Pharmaceutical Sciences, 2022)
Direct-acting antivirals used in the treatment of hepatitis C have demonstrated high rates of efficacy, are well tolerated and considered safe. However, they are not free of drug interactions. To describe the effectiveness of hepatitis C treatment and the incidence and severity of potential drug interactions between drugs used during this treatment. A cross-sectional study with 148 patients who began treatment for hepatitis C between April and June 2016 in a specialized center in Brazil. Drug interactions were identified in the Truven Health Analytic/DynaMed Plus and Hep-C Interactions databases. Regarding treatment outcome, 93.9% of patients achieved SVR, 2.7% relapsed and 3.4% did not return after the end of the follow-up period. A total of 328 chronic diseases were identified (71 different diseases), and 88.5% of the patients had at least one chronic disease. The patients reported the use of 474 drugs (121 different drugs), with 3.2 drugs per patient on average. We identified 265 potential drug interactions, classified as important (6.0%), with clinical significance (20.7%) and without clinical significance or with insufficient data (69.4%). Cirrhotic patients had a higher average number of potential drug interactions than non-cirrhotic patients (2.51 x 0.79, p = 0.000). Hepatitis C treatment with direct-acting antivirals are effective and safe for most of patients.